The effect of Intravenous House Ultra Dressing in reducing Phlebitis Associated with Peripheral Intravenous Cannulation in Pediatric patients: Randomized Controlled Trial (RCT) - Mohammed, Roaa Qaseem; Mohammed, Asmahan Qasim (Journal of Neonatal Surgery, 2025)
Background: Phlebitis is a common complication associated with peripheral intravenous (IV) cannulation in pediatric patients, often leading to discomfort, and it can result in pain, swelling, and complications that may prolong hospitalization. Objective: to determine the effect of intravenous (I.V.) House Ultra Dressing in reducing phlebitis associated with peripheral intravenous cannulation in pediatric patients. Methodology: It was a comparison and prospective randomised controlled trial (RCT). The study looked at 64 participants (2–34 months old) who were getting peripheral intravenous cannulation in paediatric wards. Randomly, 32 patients were put into the study group (Intravenous House Ultra Dressing) and 32 patients were put into the comparison group. Scores for phlebitis were kept for both groups. The Visual Infusion Phlebitis Scale (VIPS) was used to measure the severity of phlebitis, and scores were recorded every 8 to 12 hours from the start of intravenous treatment until the catheter was removed. Results: The study showed a P-value of 0.000, which means that there were statistically significant differences between the study and control groups in terms of scores and signs of phlebitis. During the three days, there were big changes between the study group and the control group compared to both groups. Conclusion: The statistically significant differences observed between the study and control groups across all three days (p-value = 0.000) indicate that this I.V. House Ultra Dressing significantly reduces the severity and scoring of phlebitis and improves intravenous site stability.